Optimalisasi Produksi Pakcoy melalui Sistem Hidroponik NFT di Rumah Kaca Berbasis Efisiensi Air dan Nutrisi - Cindona Aura Ramadhan; Davina Marsha Fadina; Muhammad Raihan Yahya; Adinda Regita Wardani; Nisrina Aprilda Conita; Najla Natasha Nisrina Ridwan; Zaskia Citra Izati; Danis Syah Nabil; Restu Puji Mumpuni; Agief Julio Pratama; M. Iqbal Nurulhaq; Ririh Sekar Mardisiwi; Ratih Kemala Dewi; Edi Wiraguna (International Forum of Researchers and Lecturers, 2026)
This article discusses the application of greenhouse technology combined with the Nutrient Film Technique (NFT) hydroponic system for Pakcoy (Brassica rapa L.) cultivation. The objective of this study is to provide an in-depth examination of Pakcoy cultivation techniques, from planting to harvesting, and to analyze the system's effectiveness in terms of land, water, and nutrient efficiency. The discussion covers the critical role of greenhouses in controlling the microclimate (temperature, humidity, and light) and protecting crops from external disturbances. In addition, the study highlights the advantages of hydroponic cultivation as a sustainable agricultural approach capable of supporting intensive vegetable production in limited spaces. The integration of greenhouse and NFT technology is expected to reduce environmental stress factors and improve crop growth consistency throughout the cultivation cycle. The results indicate that the NFT method in a greenhouse environment significantly enhances productivity and yield quality compared to conventional methods. The success of this system relies heavily on precise nutrient management (EC and pH), optimal temperature control (22–26°C), and stable nutrient flow rates to ensure a consistent supply of oxygen and nutrients to the plant roots. Overall, this cultivation model offers a promising alternative for modern and sustainable vegetable production.